Ambako Chelidze – Translator And Public Figure In Persian Poetry - Svintradze, Natia (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2016)
Ambako Chelidze was a Georgian translator and public figure. He is an interesting representative of Georgian-Persian cultural and literary relations of the 20th Century. He lived several years in Iran and dedicated his time to restoring the communication with the Fereydanian Georgians. He studied the Fereydanian dialect, life, and gained lots of experiences. He devoted the most interesting books to Fereydanian Georgians: “Fereydanian Georgians” and “Six Years in Persia” He restored the elapsed tradition of translating the Persian into Georgian and began to translate the Persian literature of the twentieth century, from which the new stage in GeorgianPersian literary relations was launched. A. Tchelidze translated Nizami Ganjevi’s poems ,,Hüsrevve ªirin”, ,,Leili and Majnun”, ,,Haft peikar”, Saadi’s ,,Bustan” and ,,Golestan”. According to the consequences after making comparison between translated and original versions the number of examples were revealed where: translator precisely scrolls the oriental elements in the Georgian text, thoroughly makes the precision and in this case we have the adequate translated version; translation consists of some changes which are not right action in our opinion, the extreme loyalty towards the original text, it’s poorly constructed in a view of fiction. Despite the fact that, there are differences between the translated version and the original text, from an artistic view translator tries to create the completed versions, which are primarily relevant to original. They are more or less valuable for Georgian readers in both artistic and cognitive views.